The risk of bleeding and all-cause mortality with edoxaban versus vitamin K antagonists: A meta-analysis of phase III randomized controlled trials. Issue 194 (October 2020) - Chen, Hai-Bin; Xiu, Jiancheng; Li, Yu-Hui; Yu, Tian-Hao
Abstract: Introduction: Edoxaban is a direct oral factor Xa inhibitor with proven antithrombotic effects. However, the risk of bleeding and all-cause mortality in patients with edoxaban versus vitamin K antagonists (VKAs) is unclear. Methods: We systematically searched all published studies of edoxaban versus VKAs. PubMed, CENTRAL databases and www.clinicaltrial.gov were searched for relevant articles published from January 1966 to 20 February 2020. All phase III randomized controlled trials (RCTs) comparing the risk of bleeding and all-cause mortality in patients with edoxaban versus VKAs were included in our meta-analysis. Both random- and fixed-effects models were used to pool data across phase III RCTs. Results: We included four trials that met our inclusion criteria ( n = 33, 077). They included patients with atrial fibrillation (3 trials, n = 24, 847), venous thromboembolism (VTE) or pulmonary embolism (PE) (1 trial, n = 8240). Edoxaban was associated with reduced risks of major or clinically relevant nonmajor bleeding (CRNM) events (OR: 0.78, 95% CI: 0.68–0.89), any bleeding events (OR: 0.76, 95% CI: 0.72–0.80), and intracranial bleeding events (OR: 0.38, 95% CI: 0.29–0.48). They had a similar risk of gastro-intestinal bleeding (OR: 0.95, 95% CI: 0.79–1.13), death from any cause (OR: 0.97, 95% CI: 0.80–1.19), stroke (OR: 1.00, 95% CI: 0.88–1.14) and systemic embolic events (OR: 0.93, 95% CI: 0.57–1.51) between edoxaban and VKAs. Conclusions: Compared to VKAs, edoxaban is safe as a direct oral anticoagulant, with respect to reduced risk of major or CRNM, intracranial bleeding events, and similar risk of gastro-intestinal bleeding events and all-cause mortality. Highlights: Edoxaban was non-inferior to VKAs with respect to the prevention of stroke or systemic embolic events. Edoxaban is associated with reduced risk of major or CRNM, intracranial bleeding events. Based on existing evidence in phase III RCTs, edoxaban is safe as a DOAC compared to VKAs.